Alternative NF‐κB Regulates RANKL‐Induced Osteoclast Differentiation and Mitochondrial Biogenesis via Independent Mechanisms. (6th August 2015) - Zeng, Rong; Faccio, Roberta; Novack, Deborah V
ABSTRACT: Mitochondrial biogenesis, the generation of new mitochondrial DNA and proteins, has been linked to osteoclast (OC) differentiation and function. In this study we used mice with mutations in key alternative NF‐κB pathway proteins, RelB and NF‐κB–inducing kinase (NIK), to dissect the complex relationship between mitochondrial biogenesis and osteoclastogenesis. In OC precursors lacking either NIK or RelB, receptor activator of NF‐κB ligand (RANKL) was unable to increase mitochondrial DNA or oxidative phosphorylation (OxPhos) protein expression, which was associated with lower oxygen consumption rates. Transgenic OC precursors expressing constitutively active NIK showed normal RANKL‐induced mitochondrial biogenesis (OxPhos expression and mitochondria copy number) compared to controls, but larger mitochondrial dimensions and increased oxygen consumption rates, suggesting increased mitochondrial function. To deduce the mechanism for mitochondrial biogenesis defects in NIK‐deficient and RelB‐deficient precursors, we examined expression of genes known to control this process. PGC‐1β (Ppargc1b) expression, but not PGC‐1α, PPRC1, or ERRα, was significantly reduced in RelB –/– and NIK –/– OCs. Because PGC‐1β has been reported to positively regulate both mitochondrial biogenesis and differentiation in OCs, we retrovirally overexpressed PGC‐1β in RelB –/– cells, but surprisingly found that it did not affect differentiation, nor did it restore RANKL‐induced mitochondrial biogenesis. To determine whether the blockade in osteoclastogenesis in RelB‐deficient cells precludes mitochondrial biogenesis, we rescued RelB –/– differentiation via overexpression of NFATc1. Mitochondrial parameters in neither WT nor RelB‐deficient cultures were affected by NFATc1 overexpression, and bone resorption in RelB –/– was not restored. Furthermore, NFATc1 co‐overexpression with PGC‐1β, although allowing OC differentiation, did not rescue mitochondrial biogenesis or bone resorption in RelB –/– OCs, by CTX‐I levels. Thus, our results indicate that the alternative NF‐κB pathway plays dual, but distinct, roles in controlling the independent processes of OC differentiation and OC mitochondrial biogenesis. Furthermore, the inability of PGC‐1β to drive mitochondrial biogenesis in OCs without RelB indicates a cell‐type specificity in mitochondria regulation. © 2015 American Society for Bone and Mineral Research.